THE CORRELATION OF LOGISTICS PERFORMANCE AND ECONOMIC CONDITION: COMPARATIVE ANALYSIS BETWEEN DEVELOPING AND DEVELOPED COUNTRIES: Received: 26th December 2023 Revised: 4th January 2024, 8th January 2024 Accepted: 2nd January 2024 - Ariowibowo, Kemal Zaki; Awokoyoa, Olajide Festus; Noveningtyas, Annisaa (PEOPLE: International Journal of Social Sciences, 2024)
Logistics sector is raising attention as previous studies have shown that it could directly affect a country’s economic condition positively. Developing countries recognizing this opportunity should be trying to pursue and improve their logistics condition so that they can catch up and mature in their own economic condition just like the developed countries. Yet, how close the gaps between are developed and developing countries if we look at the perspective of supply chain through the logistics sector. In this research, a total of 588 observations were divided and classified into 2, namely developed and developing and analyzed whether supply chain performances through logistics performance have direct correlation with that country’s economic condition and the comparative analysis the difference between the uses of the logistics sector in each classification economic condition. This research finds that supply chain performance through logistics performance do have a direct impact on a country's economic condition. However, it was also found that the impact is statistically insignificant as there are limited data samples and other variables that were not considered. This research will covet the supply chain and economic condition field of studies and this research also provides recommendation for future research.